Building and Forming the Character of the Nation Which is in Accordance with the Objectives of the Quran - Hamidah; Ade Jamarudin; Deva Dzulfikri Musthofa (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2025)
The character of education will give color to national character education. Therefore, education is a transformation towards the best educational output. All of us as children of the nation are result of education. Both through forging informal, formal and non-formal education which are the three types of education recognized in Indonesia. Our education is education that comes from heaven and is applied by looking at the reality of the earth. Qur'ani-based education is an education that will deliver people to the achievement of national peace in the future. As an intellectual, of course we don't think short that the Qur'an only discusses only regarding worship. The aim of this research is to find out the role of Qur'an in building national character. This research method uses library research and is descriptive, analytic and comparative. Source of data used in this research comes from primary and secondary data. The goal of Qur'anic character education is to produce students with Qur'anic character. In order to create people with character, students must be directed from an early age to understand the Qur'an by contemplating it; read, study, practice and teach it. The character of the Qur'anic nation is born from education that also has a Qur'anic character. Therefore, the state must provide wider space for Islamic religious education in the national law and curriculum. Because, it is a fact that Muslim students in Indonesia are more likely to get education in general education compared to religious education such as Islamic boarding schools or madrasah